UPb.age, a fast data reduction script for LA-ICP-MS U-Pb geochronology - Luigi A. Solari; Martin Tanner (Revista Mexicana de Ciencias Geológicas)
Laser ablation-inductively coupled plasma mass spectrometry (LA-ICPMS) is a rapidly growing technique that allows many different types of in-situ microanalyses to be performed in geological materials. One of the most used methodologies is U-Pb isotopic dating of accessory minerals such as zircon. These analyses can be performed at the scale of tenths of micrometers, in a rapid, cost-effective way and with very good precision and accuracy. It is critical, however, to perform the data reduction in a fast, transparent and customizable way that takes into account the specific analytical procedures employed in various laboratories and the outputs of different instruments. UPb.age is a freely available data reduction script, written and developed in R, a free statistical environment. The software can read, correct and reduce U-Pb isotopic data obtained by several LA-ICMPS instruments. Its main strengths are transparency, robustness, speed, and the ability to be readily customized and adapted to specific analytical procedures used in different laboratories.